2011
DOI: 10.1126/scisignal.2002058
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C η Is Required for T Cell Activation and Homeostatic Proliferation

Abstract: Protein kinase Cη (PKCη) is highly abundant in T cells and is recruited to the immunological synapse that is formed between a T cell and a cognate antigen-presenting cell; however, its function in T cells is unknown. Here, we showed that PKCη was required for the activation of mature CD8+ T cells by stimulation through the T cell receptor. PKCη−/− T cells showed poor proliferation in response to stimulation by antigen as compared to wild-type T cells, a trait shared with T cells deficient in PKCθ, the most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 40 publications
6
68
1
Order By: Relevance
“…The top-ranked super-enhancer in both IEL populations is adjacent to Prkch (Fig. S3B), a nonclassical Ca2 + -insensitive η-type PKC that promotes T-cell activation and cytoskeletal polarization (14,15).…”
Section: Significancementioning
confidence: 99%
“…The top-ranked super-enhancer in both IEL populations is adjacent to Prkch (Fig. S3B), a nonclassical Ca2 + -insensitive η-type PKC that promotes T-cell activation and cytoskeletal polarization (14,15).…”
Section: Significancementioning
confidence: 99%
“…This is of particular importance because initially PKCθ was the only isoform found to translocate to the TCR complex following antigen engagement (Monks et al, 1997). Recently, it has been shown that PKCη is also recruited to the immunological synapse and in similar fashion to PKCθ, can regulate [Ca 2+ ] i in T-cells (Fu et al, 2011). The activity of both of these isoforms is required for proper T-cell activation (Fu et al, 2011; Pfeifhofer et al, 2003; Sun et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that PKCη is also recruited to the immunological synapse and in similar fashion to PKCθ, can regulate [Ca 2+ ] i in T-cells (Fu et al, 2011). The activity of both of these isoforms is required for proper T-cell activation (Fu et al, 2011; Pfeifhofer et al, 2003; Sun et al, 2000). In support of an antagonistic relationship between PKC and IP 3 signaling, we noted that PMA in combination with ionomycin appeared to be less effective than ionomycin alone in decondensing chromatin in our solubility assays (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…By sharp contrast, we found recently that PKCη-deficient ( Prkch −/− ) mice exhibit a moderately immune hyperreactive phenotype indicative of an important function in T cell homeostasis (unpublished data). Prkch −/− mice that develop mild lymphadenopathy contain circulating autoantibodies, and their memory T cells display enhanced production of cytokines such as interleukin (IL)-2, IL-4 and IL-17A upon CD3/CD28 stimulation [6]. We further demonstrated that the regulatory T (Treg) cells of Prkch −/− mice are impaired in their contact-dependent suppressive activity in vitro and in vivo (unpublished data), indicating that PKCηplays a crucial part in at least one effector mechanism utilized by Treg cells and, hence, in the maintenance of T cell tolerance.…”
Section: Pkc In the Immune Systemmentioning
confidence: 99%